Strategi Digital Marketing Untuk PeningkatanDaya Saing Umkm Di Era Industri 4.0 - Berkat Putra Harefa (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
In the Industry 4.0 era, digitalization is no longer an option but a necessity for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze effective digital marketing strategies to increase the competitiveness of MSMEs amidst increasingly competitive global markets. The research methods used are literature review and descriptive qualitative analysis. The results show that the integrated use of social media, search engine optimization (SEO), and content marketing can expand market reach, increase brand awareness, and reduce operational costs. The main challenges faced are limited digital literacy and human resources, which require synergy between business actors, the government, and technology providers.